2021
DOI: 10.3390/molecules26154538
|View full text |Cite
|
Sign up to set email alerts
|

Interstrain Variability of Human Vaginal Lactobacillus crispatus for Metabolism of Biogenic Amines and Antimicrobial Activity against Urogenital Pathogens

Abstract: Lactobacillus crispatus is the dominant species in the vagina of many women. With the potential for strains of this species to be used as a probiotic to help prevent and treat dysbiosis, we investigated isolates from vaginal swabs with Lactobacillus-dominated and a dysbiotic microbiota. A comparative genome analysis led to the identification of metabolic pathways for synthesis and degradation of three major biogenic amines in most strains. However, targeted metabolomic analysis of the production and degradatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 53 publications
(58 reference statements)
2
11
0
Order By: Relevance
“…With ethical issues surrounding the supplementation of live microorganisms to infants, such an intervention would require proof of the strain's necessity in addition to rigorous safety testing. We have recently shown for Lactobacillus crispatus that metabolomic analysis can identify strains appropriate or not for probiotic applications to improve vaginal health [30]. It might not seem to be a relevant topic for a female infant but debilitating urinary tract infections can occur at that age [31].…”
Section: Why a Focus On Bifidobacterium?mentioning
confidence: 99%
See 1 more Smart Citation
“…With ethical issues surrounding the supplementation of live microorganisms to infants, such an intervention would require proof of the strain's necessity in addition to rigorous safety testing. We have recently shown for Lactobacillus crispatus that metabolomic analysis can identify strains appropriate or not for probiotic applications to improve vaginal health [30]. It might not seem to be a relevant topic for a female infant but debilitating urinary tract infections can occur at that age [31].…”
Section: Why a Focus On Bifidobacterium?mentioning
confidence: 99%
“…To date, some evidence exists to show that probiotic supplementation is sufficient to normalize the gut microbiota of C-section babies [61,62]. If this is true, then the early intervention of well-selected probiotic strains in these infants may provide a healthier start to development and prevent some of the chronic illnesses associated with microbial dysbiosis later in life [15,17,30,31,39,60]. However, investigations to elucidate which strain(s) are most effective remain to be conducted.…”
Section: Primary Colonization and Shaping Microbial Composition In The Gutmentioning
confidence: 99%
“…We previously characterized several clinical L. crispatus strains in terms of their potential to degrade and/or produce biogenic amines, while all of them have the genes for both functions, only a few were able to reduce the amount of amines in growth media. This formed the basis for selecting the strains for the present study [13]. Of significant note, L. crispatus ATCC 33820 and five vaginal L. crispatus isolates showed statistically significant reduction of putrescine, cadaverine and tyramine within 24 h. The exception was strain RL12 which increased tyramine.…”
Section: Discussionmentioning
confidence: 98%
“…It is unclear if this adaptation is pH-or metabolite-mediated. Previous studies have shown that the expression of the arginine deiminase pathway (which plays a major role in the metabolism of cadaverine and putrescine [13]) is pH-dependent in other Lactobacillus species [19]. Future studies should focus on global metabolomics and transcriptomic analyses that might identify which metabolic pathways are different between both groups and could therefore be causing these differences.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation